2017
DOI: 10.3389/fped.2017.00227
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Behavioral Disorders in Children with Neurofibromatosis Type 1

Abstract: AimThe last systematic review of research on the behavior of children with neurofibromatosis type 1 (NF1) was in 2012. Since then, several important findings have been published. Therefore, the study aim was to synthesize recent relevant work related to this issue.MethodWe conducted a systematic review of the literature. Relevant articles were identified using the electronic databases PubMed, PsycINFO, and Scopus and a manual search of references lists. Thirty of 156 articles identified met the inclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
50
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 79 publications
(160 reference statements)
3
50
1
8
Order By: Relevance
“…The NF1 gene encodes the neurofibromin protein, which serves a vital role in regulating the development of the brain [10]. Brain abnormalities have been detected in magnetic resonance imaging (MRI) studies of those with NF1, such as increased white matter volume, increased subcortical gray matter volume in the thalamus right caudate, decreased cortical gray matter density, T2 hyperintensities (T2H), macrocephaly, and reduced integrity of white matter microstructure [11][12][13]. Research has also indicated that thalamic T2H as well as volume abnormalities in the corpus callosum, putamen, and amygdala are specifically associated with cognitive deficits in NF1 [11,14].…”
Section: Neurofibromatosis Type 1 (Nf1)mentioning
confidence: 99%
See 1 more Smart Citation
“…The NF1 gene encodes the neurofibromin protein, which serves a vital role in regulating the development of the brain [10]. Brain abnormalities have been detected in magnetic resonance imaging (MRI) studies of those with NF1, such as increased white matter volume, increased subcortical gray matter volume in the thalamus right caudate, decreased cortical gray matter density, T2 hyperintensities (T2H), macrocephaly, and reduced integrity of white matter microstructure [11][12][13]. Research has also indicated that thalamic T2H as well as volume abnormalities in the corpus callosum, putamen, and amygdala are specifically associated with cognitive deficits in NF1 [11,14].…”
Section: Neurofibromatosis Type 1 (Nf1)mentioning
confidence: 99%
“…Cognitive weaknesses can present challenges for the individual, and this has been shown to occur across the lifespan [7]. Findings from studies with very young children have noted that developmental delays and subsequent academic struggles and learning disabilities are pervasive [12,20]. With regard to investigations with adults and elderly adults, cognitive weaknesses have been noted to be fairly stable over time from childhood [6,21,22].…”
Section: Neurofibromatosis Type 1 (Nf1)mentioning
confidence: 99%
“…In conclusion, subtyping both NF1 and ASD based upon prominent symptoms could be very useful. Comorbidity is very high between NF1 and ASD symptomatology on the one hand, and with ADHD symptomatology on the other hand . The former type of symptoms might benefit from methylphenidate, while the latter could improve with oxytocin or bumetanide, leading to more personalized treatment and aiming to improve the social interactions of these patients.…”
mentioning
confidence: 99%
“…Comorbidity is very high between NF1 and ASD symptomatology on the one hand, and with ADHD symptomatology on the other hand. 5 The former type of symptoms might benefit from methylphenidate, 5 while the latter could improve with oxytocin or bumetanide, leading to more personalized treatment and aiming to improve the social interactions of these patients.…”
mentioning
confidence: 99%
“…This trend is consistent with previously reported findings from the state of Victoria and with recent findings of declining CP prevalence in Europe, Japan, and the United States. [3][4][5] When stratified by gestational age categories, Galea et al found significant declines in the frequency of CP per 1000 neonatal survivors in all three geographic areas for infants born before 28 wks' gestation and in two of the three geographic areas for infants born at term. However, among all live births and neonatal…”
mentioning
confidence: 99%